1988
DOI: 10.1007/bf00225654
|View full text |Cite
|
Sign up to set email alerts
|

Further purification and partial characterization of the rat lung cytoplasmic factors modulating adenylate cyclase activity in plasma membrane

Abstract: The adult rat lung cytoplasm contains some factors which markedly stimulate adenylate cyclase activity in plasma membranes (Nijjar, M.S. Biochim. Biophys. Acta 584:43-50, 1979). Adenylate cyclase activator (ACA) was purified from rat lungs by DEAE-cellulose chromatography, preparative isoelectric focusing and by repeated high-performance liquid chromatography on a Sepharogel TSK 2000SW column. The final preparation showed about 200 fold purification in ACA activity over the original lung supernatant, and appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Earlier studies had suggested that a cytosolic cyclase-activating factor might be involved in regulating the changes in P-adrenergic responsiveness during red cell maturation (Shane et al, 1985a,b). A variety of such factors have been described previously in other tissues (Sahyoun et al, 1983;Nijjar and Khangura, 1988). Our findings are compatible with the assumption that the target of this cytosolic factor is either the ing MEL cells in the postfusion period proba 1 ly cannot catalytic subunit of the cyclase or the a-subunit of the stimulatory G protein.…”
Section: Camp Responses In Reticulocyte-mel Cell Hybridssupporting
confidence: 92%
“…Earlier studies had suggested that a cytosolic cyclase-activating factor might be involved in regulating the changes in P-adrenergic responsiveness during red cell maturation (Shane et al, 1985a,b). A variety of such factors have been described previously in other tissues (Sahyoun et al, 1983;Nijjar and Khangura, 1988). Our findings are compatible with the assumption that the target of this cytosolic factor is either the ing MEL cells in the postfusion period proba 1 ly cannot catalytic subunit of the cyclase or the a-subunit of the stimulatory G protein.…”
Section: Camp Responses In Reticulocyte-mel Cell Hybridssupporting
confidence: 92%